UW-Milwaukee Graduate School Bulletin - (:unkn) unknown (University of Wisconsin-Milwaukee Graduate School, 2002)
Program and course descriptions offered by the UW-Milwaukee Graduate School during the 2002-2003 academic year. Included in the Bulletin are administrators of the programs, lists of courses offered, descriptions of the programs and the courses offered, and information regarding the various degrees offered by graduate departments.
Keywords: Graduate School; Bulletin; Courses; Curriculum